2016
DOI: 10.7752/jpes.2016.04217
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:The purpose of this investigation was to examine the effect of a music and movement intervention program on gait, balance and psychological parameters of 10 male athletes in throwing events (ball and disc) with Cerebral Palsy (CP) (spastic hemiplegia), all coming from a sport club in Thessaloniki. Participants were divided randomly by methodical selection into two groups, the Intervention Group (IG) (n=5) and the Control Group (CG) (n=5). The IG participated in a music and movement program of 16 sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Rhythmic Auditory Stimulation gait training has been examined to some extent in adults with spastic CP ( Kim et al, 2011 , 2012 , 2020 ; Varsamis et al, 2012 ; Efraimidou et al, 2016 ), where deficits in independent walking, bilateral control, as well as pain and fatigue are often associated with a decline in mobility in the adult population. In a series of clinical studies, Kim and colleagues reported that a 3-week RAS training improved functional gait in measures such as cadence, stride length, and gait velocity, also promoting significant kinematic changes of the pelvic and hip movement ( Kim et al, 2011 , 2012 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Rhythmic Auditory Stimulation gait training has been examined to some extent in adults with spastic CP ( Kim et al, 2011 , 2012 , 2020 ; Varsamis et al, 2012 ; Efraimidou et al, 2016 ), where deficits in independent walking, bilateral control, as well as pain and fatigue are often associated with a decline in mobility in the adult population. In a series of clinical studies, Kim and colleagues reported that a 3-week RAS training improved functional gait in measures such as cadence, stride length, and gait velocity, also promoting significant kinematic changes of the pelvic and hip movement ( Kim et al, 2011 , 2012 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…This fact is confirmed by the data of the implementation of the proposed complex: performing exercises during the jogging, also counter movement jumping with the recommended dosage and adjusting to their performance contribute to the results improvement in the hammer throw (Karampatsos, 2013). The use of musical accompaniment in the preparation of athletes with cerebral palsy, whose specialization is the field-and-track throwing, provides improved psychological, and functional performance and motor skills (Efraimidou, Tsimaras, & Orologas, 2016). It is possible to improve sports results in the case of targeted impact on psychological indicators, among with the physical, technical and tactical training.…”
Section: Discussionmentioning
confidence: 56%
“…Marrades-Caballero et al ( 6 ) described improvements in the motor function of 18 children with severe CP using TIMP. Efraimidou et al ( 49 ) described the effects of a music and movement intervention program on gait, balance and psychological parameters of 10 athletes with CP, showing the relevant difficulties of these subjects.…”
Section: Discussionmentioning
confidence: 99%